2016
DOI: 10.15252/embj.201592404
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of transcriptional and cis ‐regulatory control of differentiation in human pancreatic cancer

Abstract: The histological grade of carcinomas describes the ability of tumor cells to organize in differentiated epithelial structures and has prognostic and therapeutic impact. Here, we show that differential usage of the genomic repertoire of transcriptional enhancers leads to grade-specific gene expression programs in human pancreatic ductal adenocarcinoma (PDAC). By integrating gene expression profiling, epigenomic footprinting, and loss-of-function experiments in PDAC cell lines of different grade, we identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
171
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(193 citation statements)
references
References 88 publications
22
171
0
Order By: Relevance
“…We confirmed this overall pattern of FOXA1 upregulation by RT-qPCR analysis of human PDA organoids and by immunohistochemical staining of PDA tissue derived from a rapid autopsy program (Figure S3E–G). In addition, levels of FOXA1 expression were correlated with the degree of GAIN enhancer activation in human PDA cell lines (Figure S2J) (Diaferia et al, 2016). These results validate that FOXA1 upregulation occurs during human PDA progression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed this overall pattern of FOXA1 upregulation by RT-qPCR analysis of human PDA organoids and by immunohistochemical staining of PDA tissue derived from a rapid autopsy program (Figure S3E–G). In addition, levels of FOXA1 expression were correlated with the degree of GAIN enhancer activation in human PDA cell lines (Figure S2J) (Diaferia et al, 2016). These results validate that FOXA1 upregulation occurs during human PDA progression.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have associated low FOXA1 expression with the acquisition of mesenchymal features in PDA cell lines (Diaferia et al, 2016; Song et al, 2010). However, no study to date has evaluated the functional consequences of FOXA1 upregulation in PDA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data were then compared to all of the publically available human ZEB1‐binding data for human pancreatic carcinoma Panc‐1, human hepatoblastoma HepG2, and the Gm12878 B‐lymphoblastic cell lines using the same read aligner, peak caller, and parameters (Diaferia et al ., 2016; Hensen et al ., 2014). We found that MDA‐231‐D cells and HepG2 cells had distinct profiles in terms of their ZEB1‐binding regions and that Hs578T and Panc‐1 cells, but not Gm12878 cells, shared ZEB1‐binding regions with MDA‐231‐D cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that the EMT is involved in cancer malignancy by contributing not only to metastasis but also to the acquisition of cancer stem cell properties and chemoresistance (Fischer et al ., 2015; Ye and Weinberg, 2015; Ye et al ., 2015; Zheng et al ., 2015). A recent genome‐wide analysis of EMT‐related transcription factor binding regions in pancreatic cancer cells suggested that ZEB1 plays a role in inducing the mesenchymal phenotype by suppressing enhancers that regulate the expression of epithelial genes (Diaferia et al ., 2016). However, that analysis focused only on epithelial gene expression that was related to the EMT.…”
Section: Introductionmentioning
confidence: 99%